Analisis Semiotika Roland Barthes pada Iklan IKEA: Second Best di Kanal YouTube Ads of Brands - Wijayanti, Christina Nur; Mawardiningsih, Wahjoe; Maharani I, Mathilda Regina; Harfiansyah, Hafizh (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
This study discusses the interpretation of semiotic theory in an advertisement, specifically focusing on IKEA's "Second Best" advertisement on YouTube Ads. This study aims to explore meanings beyond the product promotion intended by IKEA, examining the deeper message conveyed through the audio-visual presentation. The method used is descriptive qualitative. In this qualitative method, the author acts as the primary instrument in research, with analysis conducted continuously from the initial stages through data analysis. Semiotic analysis is the science of signs, especially from the perspective of Roland Barthes, who developed a two-tiered marking system he terms denotation and connotation. These systems can be applied to identify and understand the symbols and meanings presented in the IKEA advertisement ("Second Best"). The study results indicate a common theme, namely that IKEA seeks to offer convenience and solutions to families for their household needs, particularly through its home goods
Keywords: Semiotics of Barthes; YouTube Ads; IKEA